Application of STEM Learning with PBL and PjBL Methods to Improve Communicative Ability and Learning Outcomes of Grade 5 Students Theme 1 Organs of Movement of Animals and Humans 2021/2022 Academic Year - Ilma Fajriyah; Agustiningsih Agustiningsih; Arik Aguk Wardoyo (Pancaran Pendidikan, 2023)
One of the problems that occurred after the pandemic was the poor communication skills of students and low learning outcomes. This was caused by the approach taken by the teacher was not quite right. Therefore, it is necessary to have a learning approach that is able to improve communicative abilities and student learning outcomes. One learning approach that can be done is STEM. STEM is learning that combines science, technology, engineering and mathematics. Thus the STEM approach is used specifically as an approach using PBL and PjBL learning models as an effort to improve communicative abilities and student learning outcomes. Based on the results of the research, it is known that in class V SDN Jambekumbu 01, Pasrujambe sub-district, Lumajang, for the 2020/2021 academic year, there has been an increase in communicative abilities and student learning outcomes. Improving communicative abilities, initially achieving a classical score of 53.65 in pre-cycle, then rising to 62.5 in cycle I and 71.15 in cycle II. Learning outcomes increased from a classical score of 56.42 in pre-cycle to 70.11 in cycle I and 78.07 in cycle II.